Collaborative Governance of Public Health: A Cultural and Ethical Perspective on Predicting Citizens' Trust in Public Health Services During Medical Emergencies - Nasirin, Chairun; Winaja, I Wayan; Pratama, Arizky Farinsyah (Journal of Ethnic and Cultural Studies, 2023)
Over the years, citizens' expectations of the healthcare sector have increased, especially after the sudden outbreak of COVID-19. Additionally, citizens are becoming more conscious of having a healthier lifestyle based on several environmental and economic issues prevailing worldwide. Hence, empirically testing the predictors of providing excellent public healthcare services and enhancing the resultant citizens' trust in such services is of utmost significance. Simultaneously, the critical role of healthcare workers' capacity in providing quality services to patients in public health institutions and improving healthcare services to develop citizens' trust needs has been considered in this study. Based on a quantitative survey, the current study collected data from 460 individuals regarding three collaborative governance practices and resultant improved public healthcare services. The results revealed the significance of all three collaborative governance of public health practices. Citizen participation was the most impactful, followed by democratic accountability and procedural legitimacy. The study results are valuable to practitioners, policymakers, healthcare service providers, and governments. Among the recommendations are that collaborative governance practices should be developed, the healthcare system should be decentralized to provide the best services to citizens, and public healthcare workers' capabilities should be improved by providing proper training.